Stepping Together with Nature of Malang Raya: The Development Environmental Changes E-Book Based on Problem Based Learning (PBL) - Humaimah Nakhlah Rafidah; Fida Rachmadiarti; Muji Sri Prastiwi (Postgraduate, University of Mataram, 2024)
The development of teaching materials that are integrated with local wisdom is needed as a teaching tool to support learning using the Merdeka curriculum. To practice some of these skills, teaching materials are needed that support the application of the Merdeka curriculum for learning activities. This research aims to determine the theoretical feasibility of teaching materials in the form of environmental change e-books based on problem based learning integrated with local wisdom in Malang Raya. This research uses the ADDIE model with analysis, design, development, implementation and evaluation stages. Data was obtained from validation results by two biology lecturers and readability tests. The environmental change e-book developed has very valid criteria. The validation results are based on aspects of presentation, content, suitability of problem based learning steps. E-book readability test at level 11 or according to the level of thinking of class X high school students which is categorized as very positive and appropriate. So, it is concluded that the environmental change e-book based on problem based learning integrated with Malang Raya local wisdom is very suitable to be applied in the learning of class X high school students.